2015
DOI: 10.1097/jim.0000000000000153
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Fibroblast Growth Factor 23 and Fetuin-A with Coronary Plaque Burden and Plaque Composition in Young Adults

Abstract: The presence of subclinical CAD is independently associated with FGF-23 and fetuin-A and could be used as novel risk markers of cardiovascular disease in the asymptomatic young adult population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…FGF-23 is a bone-derived hormone whose primary role is to regulate vitamin D metabolism and renal phosphate homeostasis; meanwhile, it has been reported that FGF-23 regulates the development of cardiovascular disease by motivating nitric oxide (NO) production, endothelial nitric oxide synthase (eNOS) expression, and cell proliferation in human aortic endothelial cells ( 9 , 18 ). Moreover, a study claims that FGF-23 exhibits a higher expression in CAD patients than in non-CAD patients ( 19 ). Nevertheless, no relevant studies explore the variation of FGF-23 levels in ULMCAD patients before and after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…FGF-23 is a bone-derived hormone whose primary role is to regulate vitamin D metabolism and renal phosphate homeostasis; meanwhile, it has been reported that FGF-23 regulates the development of cardiovascular disease by motivating nitric oxide (NO) production, endothelial nitric oxide synthase (eNOS) expression, and cell proliferation in human aortic endothelial cells ( 9 , 18 ). Moreover, a study claims that FGF-23 exhibits a higher expression in CAD patients than in non-CAD patients ( 19 ). Nevertheless, no relevant studies explore the variation of FGF-23 levels in ULMCAD patients before and after CABG.…”
Section: Discussionmentioning
confidence: 99%